2001
DOI: 10.1007/s11661-001-0103-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Si and Al on acicular ferrite formation in C-Mn steel

Abstract: The influences of Si and Al on the microstructure of Ti-containing C-Mn steels have been studied. Although Si addition up to 1 wt pct did not change the crystal structure of dominant Ti 2 O 3 particles dispersed in these steels, the formation of an acicular ferrite microstructure was suppressed at high Si contents. It has been found that the Mn content dissolved in Ti 2 O 3 particles decreases with increasing Si content. This seems to weaken the formation of Mn-depleted zones (MDZs) around Ti 2 O 3 particles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…Mizoguchi and Takamura . and Shim et al observed that Al 2 O 3 inclusions cannot provide the nucleation sites for acicular ferrite. Also, no acicular ferrite is observed in S1 sample in the present research.…”
Section: Discussionmentioning
confidence: 99%
“…Mizoguchi and Takamura . and Shim et al observed that Al 2 O 3 inclusions cannot provide the nucleation sites for acicular ferrite. Also, no acicular ferrite is observed in S1 sample in the present research.…”
Section: Discussionmentioning
confidence: 99%
“…For Al 2 O 3 particle, there are some disagreements on the effects of Al 2 O 3 inclusions on the development of IAF grains. For instance, some investigations proposed that Al 2 O 3 is an anion vacancy type oxide, it is not expected to absorb surrounding Mn atoms. However, the inclusions in their literatures are isolated Al 2 O 3 without a MnS outer skin.…”
Section: Discussionmentioning
confidence: 99%
“…These inclusions were found to be inert in the present case, in accordance with most reports in the literature. [5,9,19,40,[43][44][45] 3. Steel C1 Considerable amounts of (Ti,Mn,Al,Si)O x particles were detected in steel C1.…”
Section: Steel B1mentioning
confidence: 99%